The relationship between the perceived stress of student-athletes to their training quality and sports performance satisfaction in a large public university - Jubelag, Joanna Pauline C. 2000-; Cagas, Jonathan Y. Ph.D. (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2024)
Engaging in sports has been observed to serve as both a stress-inducing factor and a gratifying physical pursuit for student-athletes. Student-athletes commonly experience stress as a necessary component of their sporting obligations. Juggling demanding training schedules, rigorous academic responsibilities, and the imperative to excel can be overwhelming. Additionally, sports provide practitioners with a means to release tension and achieve focus. This research study aims to examine the potential impact of felt stress on the training quality and sports performance of student-athletes. This study utilized a correlation research design. A cohort of student-athletes, aged between 17 to 26 years old, was recruited to complete a survey that includes the Perceived Stress Scale-10 (PSS-10), Athlete Subjective Performance Scale (ASPS), and Subjective Training Quality Scale (STQ). We incorporated six extra questions to ascertain the prevalent stressors experienced by student-athletes. The primary conjecture of this investigation posits that student-athletes who encounter elevated perceive stress levels are likely to express lower levels of training quality and sports performance satisfaction. The acquired data were organized using statistical tools designed for social sciences research. Subsequently, two separate linear regressions were performed to investigate the perceived stress levels of student-athletes and the correlation between their subjective training quality and satisfaction with sports performance. The study findings provide valuable insights into the correlation between student-athletes' perceived stress levels and their satisfaction with training quality and sports performance, highlighting stress's detrimental impact on both variables.
Vita
Thesis (Bachelor of Sport Science) -- University of the Philippines Diliman
Keywords: College athletes; Stress (Psychology); Sports -- Psychological aspects